(untitled) (Applied Biological Research, 2023)
Dengue fever, transmitted by Aedes aegypti L. (Diptera: Culicidae), is the most important disease affecting human health and economy in the western part of Saudi Arabia. This study aimed to investigate the larvicidal activities of ethanolic, acetonic and aqueous extracts prepared from the leaves of Arfaj (Rhanterium epapposum Oliv.) against dengue fevemosquito vector, Aedes aegypti, under laboratory conditions. The larvicidal potency ofethanolic extract at high concentration of 50000 ppm was up to 98% after 24 h exposure. In contrast, acetonic and aqueous extracts caused 72 and 30% larval mortality, respectively, at the same concentration and exposure time. After 48 h exposure, the mortalities increased by 99, 86 and 35%, respectively, for ethanolic, acetonic and aqueous extracts. This study showed that the ethanolic extract had a higher larvicidal effect with lower LC50 value (168.15 ppm), followed by acetone (847.75 ppm) and aqueous (2278.22 ppm) extracts after 24 h exposure. Further studies are needed to isolate and identify the primary component responsible for larvicidal efficiencyof this plant extract which may give good insights for developing a sustainable mosquito control method.